Antipsychotic Withdrawal Symptoms: A Systematic Review and Meta-Analysis - Brandt, Lasse; Bschor, Tom; Henssler, Jonathan; Müller, Martin; Hasan, Alkomiet; Heinz, Andreas; Gutwinski, Stefan (Frontiers in Psychiatry, 2020)
Objective: Avoiding withdrawal symptoms following antipsychotic discontinuation, reduction, or switch is an important factor when planning a safe and successful therapy. We performed a systematic review and meta-analysis concerning occurrence of withdrawal symptoms after discontinuation of antipsychotics. Data Sources: We searched the databases CENTRAL, Pubmed, and EMBASE with no restriction to the beginning of the searched time period and until October 1, 2019 (PROSPERO registration no. CRD42019119148). Study Selection: Of the 18 043 screened studies, controlled and cohort trials that assessed withdrawal symptoms after discontinuation of oral antipsychotics were included in the random-effects model. Studies that did not implement placebo substitution were excluded from analyses. The primary outcome was the proportion of individuals with withdrawal symptoms after antipsychotic discontinuation. We compared a control group with continued antipsychotic treatment in the assessment of odds ratio and number needed to harm (NNH). Data Extraction: We followed guidelines by the Cochrane Collaboration, PRISMA, and MOOSE. Results: 5 studies with a total of 261 individuals were included. The primary outcome, proportion of individuals with withdrawal symptoms after antipsychotic discontinuation, was 0.53 (95% CI, 0.37-0.70; I2 = 82.98%, P < 0.01). An odds ratio of 7.97 (95% CI, 2.39-26.58; I2 = 82.7%, P = 0.003) and NNH of 3 was calculated for the occurrence of withdrawal symptoms after antipsychotic discontinuation. Conclusion: Withdrawal symptoms appear to occur frequently after abrupt discontinuation of an oral antipsychotic. The lack of randomized controlled trials with low risk of bias on antipsychotic withdrawal symptoms highlights the need for further research.